WHF Recommendations for the Use of Echocardiography in Chagas Disease - Kate Ralston; Ezequiel Zaidel; Harry Acquatella; Marcia Melo Barbosa; Jagat Narula; Yu Nakagama; Gustavo Restrepo Molina; Karen Sliwa; Jose Luis Zamorano; Fausto J. Pinto; Daniel Jose Piñeiro; Mariana Corneli (Global Heart, 2023)
Chagas disease (ChD) represents a significant health burden in endemic regions of Latin America and is increasingly being recognized as a global health issue. The cardiac involvement in ChD, known as Chagas cardiomyopathy (ChCM), is the most severe manifestation and a leading cause of heart failure and mortality in affected individuals. Echocardiography, a non-invasive imaging modality, plays a crucial role in the diagnosis, monitoring, and risk stratification of ChCM. This consensus recommendation aims to provide guidance on the appropriate use of echocardiography in ChD. An international panel of experts, including cardiologists, infectious disease specialists, and echocardiography specialists, convened to review the available evidence and provide practical recommendations based on their collective expertise. The consensus addresses key aspects related to echocardiography in ChD, including its role in the initial evaluation, serial monitoring, and risk assessment of patients. It emphasizes the importance of standardized echocardiographic protocols, including the assessment of left ventricular function, chamber dimensions, wall motion abnormalities, valvular involvement, and the presence of ventricular aneurysm. Additionally, the consensus discusses the utility of advanced echocardiographic techniques, such as strain imaging and 3D echocardiography, in assessing myocardial mechanics and ventricular remodeling.